Technical Analysis of 2007 and 2017 World Taekwondo Women and Men Championship Finals - Sevde Mavi Var (Türk Spor ve Egzersiz Dergisi, 2018)
Purpose of this study is to compare the latest world championships with the old system and the latest world championship competitions with the new system, and to compare the competitions in two different systems by conducting activity and technical analysis. Thus, the technical analysis of the 2007 and 2017 world taekwondo championship women's and men's finals was performed. SPSS 22.0 package program was used for statistical analysis of the acquired data and results were evaluated at p lt;0.05 significance level. Mann - Whitney U Test was applied to the techniques used (punch, palding, pusachagi, yopchagi, dwichagi, neryochagi, dollyochagi, pandedollyo), total technical numbers, frequency and percentage analysis of points and penalties and pairwise comparisons. When the findings of the study were examined, there were statistically meaningful differences found between the number of techniques used in the competition and the techniques used in the competitions in 2017 (women; p = .001, men; p = .001). In the world championship finals in 2007, while women athletes used a total of 404 techniques, they used 1152 techniques in the world championship finals in 2017. In 2007, totally 525 techniques were used in men and in 2017, 1205 techniques were used. As a conclusion, in Taekwondo, when the competitions between the old system and the new system are compared, it can be said that in the new system, the athletes use much more techniques and their scores increase considerably depending on the changing rules and the technical numbers.